Financial Information System at the Sumba Christian Church Web-Based Wainggai Congregation - Ndapa Otu, Toni Yiwa; Hariadi, Fajar; Sitaniapessy, Desy Asnath (Yayasan Kita Menulis, 2025)
Financial information systems are information systems designed to provide users with information about cash flows throughout an organization. The procedures carried out in this system are a series of written documents or actions involving many people in a department to ensure consistent treatment. The Sumba Christian Church (GKS) Wainggai Congregation currently does not have information technology that can help to summarize church finances, so that errors often occur from the congregation when examining the treasurer. Because the calculation or addition of church finances every month is often wrong, so each income and expense must be recalculated from the beginning of the month. From certain problems, using information technology can help alleviate complaints or problems that often occur. Therefore, it is necessary to create an information system at the GKS Wainggai Congregation to help manage church finances so that errors do not occur again. This study uses the prototype method.The results of testing using the blackbox method show that this system can run according to its function without any errors. Meanwhile, from the results of the SUS test that has been carried out from the level of user satisfaction with the church's financial recording information system, the assessment given to 1o respondents resulted in a score of 78%. With acceptability ranges